2024
DOI: 10.3390/microorganisms12020390
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analysis of Antarctic Ocean near the King Sejong Station Reveals the Diversity of Carotenoid Biosynthetic Genes

Woo Yeon Cho,
Pyung Cheon Lee

Abstract: Carotenoids, biotechnologically significant pigments, play crucial biological roles in marine microorganisms. While various environments have been explored to understand the diversity of carotenoids and their biosynthesis, the Antarctic Ocean remains relatively under-investigated. This study conducted a metagenomic analysis of seawater from two depths (16 and 25 m) near the King Sejong Station in the Antarctic Ocean. The analysis revealed a rich genetic diversity underlying C40 (astaxanthin, myxol, okenone, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In the case of enzyme detection in marine environments, marine sediments have been used frequently, where it has been shown that there is a greater microbial diversity and that they are even more phylogenetically diverse than other environmental types including the soil [136,137], for pigments metagenomics also has wide use to explore the diversity of pigments that can be found in the deep sea at different depths, as shown by Cho et al [138], they indicate depth dependent variations in carotenoid biosynthesis pathways, for example, The astaxanthin as it is mentioned above helps against UV radiation, but in the case of the microorganisms studied, variations on it are observed according to the depth.…”
Section: Metagenomicsmentioning
confidence: 99%
“…In the case of enzyme detection in marine environments, marine sediments have been used frequently, where it has been shown that there is a greater microbial diversity and that they are even more phylogenetically diverse than other environmental types including the soil [136,137], for pigments metagenomics also has wide use to explore the diversity of pigments that can be found in the deep sea at different depths, as shown by Cho et al [138], they indicate depth dependent variations in carotenoid biosynthesis pathways, for example, The astaxanthin as it is mentioned above helps against UV radiation, but in the case of the microorganisms studied, variations on it are observed according to the depth.…”
Section: Metagenomicsmentioning
confidence: 99%